Trends in Medicare Physician and Facility Fee Reimbursement in Orthopaedic Foot and Ankle - Clayton Hui; Haroon Kisana; John R. Martin; Chad Stecher; Joshua Hustedt MD (Foot & Ankle Orthopaedics, 2022)
Category: Ankle; Ankle Arthritis; Arthroscopy; Bunion; Diabetes; Hindfoot; Lesser Toes; Midfoot/Forefoot; Sports; Trauma Introduction/Purpose: The purpose of the study was to examine the trends in physician and facility reimbursement for the orthopaedic foot and ankle subspecialty utilizing the 23 most common foot and ankle surgeries based on national payment amounts. Methods: The Current Procedural Terminology (CPT) codes and corresponding Medicare Severity - Diagnosis Related Group (MS-DRG) codes for the 23 most common orthopaedic foot and ankle surgeries were identified. With the CPT codes, physician reimbursement was obtained through querying the Medicare Physician Fee Schedule (MPFS) for the work, malpractice, and practice expense relative value units (RVU) and then multiplying the total RVUs by the yearly conversion factor. CPT codes were also utilized to gather hospital outpatient reimbursement data from the Hospital Outpatient Prospective Payment System (OPPS) database. Hospital inpatient reimbursement rates were obtained from the Hospital Inpatient Prospective Payment System (IPPS) database utilizing the MS-DRG codes. All amounts were then adjusted for inflation using the Consumer Price Index (CPI). Results: From 2008 to 2021, physician reimbursement for the 23 most common orthopaedic foot and ankle surgeries decreased by 20%, with a mean Compound Annual Growth Rate (CAGR) of -1.7%. Hospital inpatient reimbursement increased by 34.7% with a mean CAGR of 2.3%; while outpatient hospital reimbursement increased by 97.2% with a mean CAGR of 5.1%. Conclusion: Over the past 13 years, physician reimbursement for common orthopaedic foot and ankle surgeries has declined while hospital reimbursement has increased. The larger increase in outpatient reimbursement compared to inpatient reimbursement highlights how CMS aims to transition surgeries from the inpatient setting to the more efficient and less expensive outpatient setting. This downward pressure on physician reimbursement while incentivizing outpatient services could have many unintended consequences on the landscape of foot and ankle practice in the US.